Analysis of Value-Added Tax Restitution on Exports at PT Rama global in 2019 - Alian Natision; Cindy Anggraini; Novianita Rulandari; Redjeki Agoestyowati (Ilomata International Journal of Tax and Accounting, 2021)
PT Rama Global is a trading company that carries out preliminary restitution under certain conditions. The purpose of this paper is to find out how the preliminary restitution with certain requirements in the context of tax planning is carried out by PT. Rama Global, how are the obstacles faced in making tax refunds, and what efforts are being made to deal with these obstacles. The method used is a qualitative method with data collection techniques, namely interviews, observation, documentation, and triangulation. Based on observations, PT Rama Global is an export company that input tax is greater than the output tax. PT Rama Global chose to restitute the tax with preliminary restitution, but there will be some refunds that cannot be withdrawn, so PT Rama Global confirms the transaction with the counterparty.